Long-term survival following laparoscopic and open colectomy for colon cancer: a meta-analysis of randomized controlled trials - Theophilus, Mary; Platell, Cameron; Spilsbury, Katrina (Wiley, 2014)
Aim: Large randomized clinical trials comparing long-term survival after laparoscopic and open colectomy for large bowel cancer show equivalence, but meaningful analysis of data by stage has not been possible due to the small numbers of patients in individual trials. The aim of this meta-analysis was to improve statistical power by combining data to enable assessment of survival for individual stages. Method: A systematic review and meta-analysis was conducted through a computerized search of all randomized controlled trials comparing open and laparoscopic surgery for large bowel cancer. Overall survival data were analysed and subgroup analysis was performed for cancer of Stages I–III. Results: Five trials (3152 patients) were included. Overall survival was equivalent (hazard ration 0.93; 95% confidence interval 0.80–1.07). With each of the cancer stages, I–III, there was no difference in 5-year survival. There was, however, a nonsignificant trend in favour of open surgery in the subgroup analysis of Stage II patients. Conclusion: Laparoscopic-assisted surgery for colon cancer is equivalent to open surgery with respect to long-term survival although there may be a difference for Stage II cancer.